Ladybird Larvae, Coelophora Bisselata Mulsant (Coleoptera: Coccinelladae) as a Source of Fibrinolytic Enzyme - Choudhury, Parichita Ray; Saha, Susmita; Sil, Samir Kumar (Asian Journal of Biological and Life Sciences, 2016)
The combination of traditional knowledge and advanced biotechnology can explore the bio-prospects of biological resources as a new source of drug or medicine and thus can promote the sustainable utilization of biodiversity. Insects belong to a diverse Class and thus their biodiversity can be contributed for exploitation of incredible variety of bio active ingredients. Though there have been few studies on the antibacterial potential of ladybird species, no report is being made on the fibrinolytic activity of ladybird larvae till date. In the present study, we for the first time evaluated the in vitro fibrinolytic activities of crude extracts from larvae as well as adult ladybird, Coelophora bisselata. The ladybird, C. bisselata (Coleoptera: Coccinelladae) is a cosmopolitan polyphagous predatory beetle which is often used as biocontrol agents against many economically important pest species. The fibrinolytic activity was tested using fibrin plate method. Results showed that larvae extract possessed profound fibrinolytic activity. However, in the extract from adult form no such activity was observed. The study suggested that crude extracts from larvae of C. bisselata might prove to be useful alternative source for the development of new drugs for treatments involving blood coagulation and fibrinolysis.
Keywords: Coelophora bisselta; Fibrinolytic activity; Insect crude extract